2021
DOI: 10.3389/fpsyt.2021.573168
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sugar-Sweetened Beverages, Takeaway Dietary Pattern, and Psychological and Behavioral Problems Among Children and Adolescents in China

Abstract: Background and Aim: The association of sugar-sweetened beverage (SSB) consumption and takeaway dietary pattern with psychological problems in Chinese children and adolescents has not been concretely reported. Our study aimed to investigate the association between SSB consumption, takeaway dietary pattern, and psychological and behavioral problems (PBPs).Methods: Cluster sampling method has been adopted from April to May 2019 to conduct a questionnaire survey among 30,188 children and adolescents in grades 1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Similarly, increased consumption of SSBs has been linked to depression and mood disorders in a cognate study in London, UK. Research on SSB consumption maintained that a lower intake of raw sugar and nonnutritive sweeteners (NNS) such as aspartame, saccharin, sucralose, neotame, acesulfame-K, and stevia may be associated with better psychological and physical health outcomes [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increased consumption of SSBs has been linked to depression and mood disorders in a cognate study in London, UK. Research on SSB consumption maintained that a lower intake of raw sugar and nonnutritive sweeteners (NNS) such as aspartame, saccharin, sucralose, neotame, acesulfame-K, and stevia may be associated with better psychological and physical health outcomes [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…SSBs such as carbonated beverages and sugar-sweetened fruit juice beverages, were suggested to have an association with an increased risk of children’s physical health problems, including dental caries, obesity(s) and other metabolic diseases ( 4 , 5 ). Some previous studies suggested that SSB consumption was linked with mental problems, such as impaired cognitive function ( 6 , 7 ), executive function (EF) ( 8 ), as well as behavioral problems, including hyperactivity problems and emotional symptoms ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The way in which dietary patterns are derived and assessed by questionnaires is also crucial, such as the frequency of food intake and the assessment of portion size. A clear gap in the literature on diet and child behaviour is that most of the research has only focused on frequency of food intake, rather than the actual portion (quantity) of food consumed (Ajmal et al, 2022;Zhang et al, 2021). For example, one study asked, "How many times do you eat takeaways each week", the answers ranged from "never" to "high frequency" (Zhang et al, 2021).…”
Section: Dietary Patternsmentioning
confidence: 99%
“…A clear gap in the literature on diet and child behaviour is that most of the research has only focused on frequency of food intake, rather than the actual portion (quantity) of food consumed (Ajmal et al, 2022;Zhang et al, 2021). For example, one study asked, "How many times do you eat takeaways each week", the answers ranged from "never" to "high frequency" (Zhang et al, 2021). However, the portion of the food consumed was not included within the questionnaire.…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation